A violência entre jovens num colégio de Foz do Iguaçu - Araújo, Irani Batista de (2015)
The objective of the research is to analyze the violence among adolescents in a school of Porto Belo neighborhood of Foz do Iguaçu / PR. The interest came from situations experienced in the school environment in the region for a period of two years. There were many press reports involving youth in the region, in addition to the situations of physical and verbal attacks witnessed within the institution. Several interviews were conducted with students, faculty, staff and local residents addressing the issue at hand. In addition to the theoretical development through the study of books, essays and articles which reflect the theme of violence in the broad sense and adolescence, it was found, by means of joint research instrument, the reasons that induce students to get involved in conflicts . For better access to the phenomenon researched statistical data were verified civil police about the killings in the region, the School Patrol and analysis of Minutes books from the university to better describe the violence, and against the school. Thus, it is expected that the research work can contribute to a better understanding of the phenomenon of interest.